KNOWLEDGE AND PRACTICES REGARDING BIO-MEDICAL WASTE MANAGEMENT AMONG STAFF NURSES IN TERTIARY CARE HOSPITAL - ILYAS , M; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Biomedical waste (BMW) management is a critical aspect of healthcare delivery, ensuring safety for healthcare workers, patients, and the environment. In Pakistan, the implementation of effective BMW management practices remains a significant challenge due to limited resources and inconsistent adherence to protocols. Objective: To evaluate the knowledge and practices of staff nurses regarding BMW management in a tertiary care hospital in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 130 female nurses. Data were collected using a structured questionnaire assessing knowledge and practices related to BMW management. Descriptive statistics, including frequencies and percentages, were analyzed using SPSS version 26. Results: All participants (100%) were aware of BMW generation and legislation, and 96.9% adhered to colour-coded waste segregation. However, only 82.3% used puncture-proof containers for sharps disposal, and 87.7% were aware of the preparation of disinfectant solutions. Most nurses (99.2%) reported wearing PPE, and 92.3% were immunised against Hepatitis B. Despite these strengths, gaps in adherence to storage time limits and sharp disposal protocols were noted. Conclusion: While awareness and adherence to certain BMW management practices were high, significant gaps remain in compliance with critical protocols. Enhanced training, monitoring, and resource provision are essential to ensure safe and effective BMW management in healthcare settings in Pakistan.